PROFIL DERMATOFITOSIS DI POLIKLINIK KULIT DAN KELAMIN RSUP SANGLAH DENPASAR PERIODE 2017 -2018 - Kadek Ena Septiani Surya Puspita Sari (E-Jurnal Medika Udayana, 2021)
Abstract: Dermatophytosis is skin infection caused by dermatophytes colonization in keratinized tissue, such as stratum corneum of epidermis, nails and hair. The aims of study are to evaluate the characteristic of patients and species causing dermatophytosis in Mycology division Outpatient Clinic Sanglah General Hospital Bali in 2017 and 2018 periods. This descriptive retrospective study done by taking consecutive sampling in order to evaluate dermatophytosis characteristic according to diagnosis, age, sex, and organisms isolate from culture examination. Dermatophytosis new cases decreasing from 9,5% in 2017 to 7,9% in 2018. The most common diagnosis are tinea unguium (45,3%) and tinea cruris (25,7%) with Trichophyton rubrum (34,8%) and Trichophyton mentagrophytes (20,2%) species mostly isolated from culture examination. Male (59%) and 45-64 years old age group (35,8%) are the most common groups diagnose with dermatophytosis. Keywords: Dermatophytosis, tinea, descriptive retrospective study